2019
DOI: 10.47176/mjiri.33.77
|View full text |Cite
|
Sign up to set email alerts
|

Interventions on reducing burnout in physicians and nurses: A systematic review

Abstract: Background interventions c The present stu physicians and Methods: St Randomized cl were included. excluded. Results: Bas included studie approach, and Nevertheless, s Conclusion: teamwork, par interventions c interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
83
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(90 citation statements)
references
References 0 publications
3
83
0
4
Order By: Relevance
“…When compared with other recently published systematic reviews [17][18][19]28,50,51], this paper is unique, as, to our knowledge, it is the only review with PIMs as an intervention, which is an added value, compared with those solely focusing on the duration of MBSR's effects.…”
Section: The Sustained Effect Of Psychological Interventions With Elements Of Mindfulnessmentioning
confidence: 98%
“…When compared with other recently published systematic reviews [17][18][19]28,50,51], this paper is unique, as, to our knowledge, it is the only review with PIMs as an intervention, which is an added value, compared with those solely focusing on the duration of MBSR's effects.…”
Section: The Sustained Effect Of Psychological Interventions With Elements Of Mindfulnessmentioning
confidence: 98%
“…(21,23) However, no study in our systematic review used interventions such as yoga or cognitive therapy to improve junior doctor wellbeing, as documented in earlier systematic reviews including studies performed in other countries. (21,24) It is widely recognised that Randomised Control Trials (RCTs) are the gold standard to demonstrate effectiveness of an intervention. (41) However, we acknowledge that RCT may not always be plausible.…”
Section: Discussionmentioning
confidence: 99%
“…(19,23) Additionally, organisational changes in other countries have been identi ed as more effective in improving physician wellbeing when compared to the interventions documented in UK-based studies. (19,24) Some authors are now recommending that in addition to wellbeing interventions, other organisational protective strategies such as increasing departmental sta ng, good leadership and diversi cation of activities (including teaching and research) should be considered. (42) Moreover, the recent COVID-19 pandemic has also demonstrated that wellbeing interventions need to be holistic because factors impacting on the wellbeing of newly-quali ed doctors are not only inherent in the FY and CT training programmes, but may equally be organisationally-related.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interventions and a burnout prevention model must be established to mitigate nursing personnel burnout (Aryankhesal et al, 2019). The objective of this study is to establish a model that illustrates the relationships among WFC, burnout, and the supervisor support received by nursing personnel, which have been supported by much literature (Lee, Kim, Park, & Yun, 2013; Yang, Liu, Liu, Zhang, & Duan, 2017).…”
Section: Introductionmentioning
confidence: 99%